[Rezension von: Daniel Perret (Hrsg.), Writing for eternity] - Jákl, Jiří (Bijdragen tot de taal-, land- en volkenkunde, 2020)
"Writing for Eternity: A Survey of Epigraphy in Southeast Asia, by Daniel Perret (ed.)" published on 06 Nov 2020 by Brill.
Gesehen am 10.12.2020
Keywords: Rezension